Seeding solutions: Volume 2. Options for national laws governing control over genetic resources and biological innovations - Crucible II Group (2001)
It is a very practical tool that national policy-makers can use to address the issues raised in Volume 1. It consists of annotated collections of optional legislative provision for national laws to regulate access to genetic resources and to create various forms of intellectual property protection for plant varieties, biological innovations, and indigenous and local knowledge. While not written to be adopted into any country's national laws in their current form, these provisions provide an excellent means by which policy-makers can assess the range of choices before them.